1989
DOI: 10.2165/00003495-198938050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide

Abstract: Octreotide is an analogue of somatostatin. Like endogenous somatostatin, it exerts a potent inhibitory effect on the release of anterior pituitary growth hormone and thyroid-stimulating hormone, and peptides of the gastroenteropancreatic endocrine system, while overcoming some of the shortcomings of exogenously administered somatostatin, namely a short duration of action, a need for intravenous administration and postinfusion rebound hypersecretion of hormone. Clinical studies have shown that octreotide is eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(19 citation statements)
references
References 147 publications
0
19
0
Order By: Relevance
“…The mechanism by which somatostatin analogues normalize bowel function is not clear, however, it is hypothesised that involves inhibition of gut hormone secretion, lengthening of intestinal transit time, increased water and electrolyte absorption and reduced splanchnic blood flow[23-26]. Treatment with octreotide improves survival in patients with carcinoid crisis[27].…”
Section: Somatostatine Analogs: Past Present and Futurementioning
confidence: 99%
“…The mechanism by which somatostatin analogues normalize bowel function is not clear, however, it is hypothesised that involves inhibition of gut hormone secretion, lengthening of intestinal transit time, increased water and electrolyte absorption and reduced splanchnic blood flow[23-26]. Treatment with octreotide improves survival in patients with carcinoid crisis[27].…”
Section: Somatostatine Analogs: Past Present and Futurementioning
confidence: 99%
“…Octreotide suppresses the release of growth hormone, prolactin and various hormones of the gastro-entero-pancreatic endocrine system, thereby regulating intestinal and pancreatic secretory processes. It is used clinically in the therapy of acromegaly and in the symptomatic treatment of carcinoid syndrome or endocrine tumours of the GI tract (Del Pozo, 1988;Battershill & Clissold, 1989). Recent studies in healthy volunteers have demonstrated that octreotide effectively suppresses plasma insulin levels after oral administration, indicating that functionally active peptide is absorbed (Williams et al, 1986;Fuessl et al, 1987), despite its rather low systemic bioavailability of about 0.3% (Kohler et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, octreotide has been frequently used in the treatment of acromegaly, due to its inhibitory actions on growth hormone and insulin-like growth factor 1 secretion. [67] Growth hormone level was suppressed in 2 children treated with octreotide for 3–4 weeks. [2451] The concern that octreotide may cause growth retardation on long-term use has been refuted by several studies.…”
Section: Discussionmentioning
confidence: 99%